MicroRNAs as Biomarkers for the Diagnosis of Ankylosing Spondylitis: A Systematic Review and Meta-Analysis - Li, Jiangbi; Xie, Xiaoping; Liu, Weibing; Gu, Feng; Zhang, Ke; Su, Zilong; Wen, Qiangqiang; Sui, Zhenjiang; Zhou, Pengcheng; Yu, Tiecheng (Frontiers in Medicine, 2021)
Background: Recent studies have shown abnormal microRNA (miRNA) expression levels in ankylosing spondylitis (AS), suggesting that miRNAs may serve as promising biomarkers for AS. In this study, we conducted a meta-analysis to identify the potential usefulness of miRNA biomarkers in the diagnosis of AS. Methods: An extensive search was undertaken in PubMed, Embase, Cochrane databases and Wan Fang databases up to 30 December 2020 using the following key words: (“microRNAs” or “microRNA” or “miRNA” or “miR” or “RNA, Micro” or “RNA, Micro” or “Primary MicroRNA”) and (‘‘Spondylitis, Ankylosing’’ or ‘‘Spondyloarthritis Ankylopoietica’’ or “Ankylosing Spondylarthritis” or “Ankylosing Spondylarthritides” or “Spondylarthritides, Ankylosing” or “Ankylosing Spondylitis”) and (“blood” or “serum” or “plasma”), statistical evaluation of dysregulated miRNAs using sensitivity, specificity, positive likelihood ratio(PLR), positive likelihood ratio(NLR), diagnostic odds ratio (DOR), and area under the curve (AUC) was performed. Results: Twenty-nine articles investigating miRNAs of AS were included. A total of 87 miRNAs were found to be either upregulated (n = 42) or downregulated (n = 45) in AS cases as compared with controls. Besides, 29 studies from nine articles were included in the current meta-analysis with a total of 496 AS patients and 383 controls. The pooled sensitivity, specificity, PLR, NLR, DOR, and AUC were 0. 76 （95% CI, 0.70-0.81）, 0.80 (95% CI, 0.74-0.85）, 3.75 (95% CI, 2.82-5.01), 0.31 (95% CI, 0.24-0.39), 12.32 (95% CI, 7.65-19.83), 0.85 （95% CI, 0.81-0.88）, respectively, indicating good discriminative ability of miRNAs as biomarkers for AS.